2022
DOI: 10.1007/s11136-022-03095-1
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between physical and mental health multimorbidity and children’s health-related quality of life

Abstract: Purpose To examine the relationships between physical health problems, and borderline or clinical levels of mental health symptoms and children’s health-related quality of life (HRQoL). Methods Data were from the Longitudinal Study of Australian Children (2004–2018). Parents reported on their child’s HRQoL (PedsQL), physical health problems and mental health symptoms (Strengths and Difficulties Questionnaire, SDQ). A pooled cross-sectional analysis using l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 50 publications
1
9
0
Order By: Relevance
“…The HrQoL was reduced by half among those with borderline and abnormal internalizing problems and a 40% reduction among those externalizing problems. This finding is supported by previous evidence in Nigeria [ 40 ], Kenya [ 41 ], Rotterdam [ 42 ], Australia [ 43 ], and in the United States [ 44 ], which revealed that the HrQoL of adolescents with mental health problems is strongly affected and functionally inferior even in comparison with adolescents with other health problems. One possible explanation for the strong association of internalization and externalization of mental health problems on HrQoL is that the internalization and externalization of mental health problems affect the functioning of adolescents in multiple ways.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The HrQoL was reduced by half among those with borderline and abnormal internalizing problems and a 40% reduction among those externalizing problems. This finding is supported by previous evidence in Nigeria [ 40 ], Kenya [ 41 ], Rotterdam [ 42 ], Australia [ 43 ], and in the United States [ 44 ], which revealed that the HrQoL of adolescents with mental health problems is strongly affected and functionally inferior even in comparison with adolescents with other health problems. One possible explanation for the strong association of internalization and externalization of mental health problems on HrQoL is that the internalization and externalization of mental health problems affect the functioning of adolescents in multiple ways.…”
Section: Discussionsupporting
confidence: 87%
“…The results showed that all chronic physical conditions were associated with poor HrQoL in adolescents. Previous studies have also reported that any chronic physical disorder affects HrQoL in adolescents [ 25 , 43 ]. The potential explanation for this association could be chronic physical disease can have a broad impact, including HrQoL, which measures the impact of a young person’s health on their everyday emotional, social and physical functioning [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is crucial to measure domains of health in adolescents to prevent more serious longterm conditions [17]. Lower health-related quality of life has been associated with high mental health symptoms in adolescents and therefore health-related quality of life should be explored in this population [18].…”
Section: Introductionmentioning
confidence: 99%
“…The LSAC data has been used extensively to explore various aspects of child wellbeing through longitudinal analysis (e.g. Howard & Williams, 2018;Mishra et al, 2017;O'Loughlin et al, 2022;Wang et al, 2019;Warren, 2017). For example, in developing a longitudinal multidimensional poverty index based on the UN Convention on the Rights of the Child, Mishra et al (2017) found that health and emotional wellbeing were the largest areas of concern, driven predominantly through poor body weight and bullying.…”
Section: Introductionmentioning
confidence: 99%